A refuge between houses and buildings: reptiles in a peri-urban Atlantic Forest fragment in northeastern Brazil - Marcos-J-M Dubeux; Ubiratan Gonçalves; Tamí Mott (Caldasia)
The Atlantic Forest is recognized as a global biodiversity hotspot, but despite the comparatively large number of published reptile inventories already available for this region, large geographic gaps remain unfilled. The purpose of this paper is to provide a list of reptile species recorded in the Área de Proteção Ambiental doCatolé e Fernão Velho (APACFV), a 37 km2 peri-urban protected area in the northern Atlantic Forest in the Brazilian state of Alagoas. Based on a review of reptile specimens and photo-graphs collected over 27 years, a total of 65 species belonging to three orders and 22 families occur in the APACFV: three turtle families (4 spp.), one alligator family (2 spp.), 12 non-snake lizard families (24 spp.), and six snake families (35 spp.). Despite the imperilment of the biota of this region, only one of the recorded species is included on the endangered species list of the Brazilian government (Amero-typhlops paucisquamus, Vulnerable), and none are categorized as threatened under the Red List of Threatened Species of the International Union for Conservation of Nature. The reptile assemblage in the APACFV is among the most diverse documented for Alagoas, and this list is an important step to inform management strategies in this protected area.